2019
DOI: 10.3390/jcm8060778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthetic Technique on the Occurrence of Acute Kidney Injury after Total Knee Arthroplasty

Abstract: Recent studies have reported the advantages of spinal anesthesia over general anesthesia in orthopedic patients. However, little is known about the relationship between acute kidney injury (AKI) after total knee arthroplasty (TKA) and anesthetic technique. This study aimed to identify the influence of anesthetic technique on AKI in TKA patients. We also evaluated whether the choice of anesthetic technique affected other clinical outcomes. We retrospectively reviewed medical records of patients who underwent TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…Our study has some limitations. First, there were inevitable flaws due to the nature of the retrospective observational design ( 51 ). Second, there were a relatively limited number of patients enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has some limitations. First, there were inevitable flaws due to the nature of the retrospective observational design ( 51 ). Second, there were a relatively limited number of patients enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Both spinal anaesthesia and general anaesthesia are safe and effective in TKA patients. Previous studies reported that spinal anaesthesia reduces the risk of acute kidney injury, vascular and pulmonary complications, postoperative pain, and opioid-related adverse effects [17,18]. These results were partially explained by varying influences of anaesthetic techniques on the biological stress response to surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have put forward the hypothesis that compared with general anesthesia, spinal anesthesia can entirely block the sympathetic nerves at the surgical site, reduce the tension of the renin-angiotensin system, increase renal blood ow and urine output. 16,17 The PNB technique can also soothe the sympathetic tension by blocking the peripheral nerve afferent while maintaining the blood vessels' self-regulating capabilities, preserving the stability of the circulatory system, and maintaining perfusion of the vital organs.…”
Section: Discussionmentioning
confidence: 99%
“…They found that patients that received spinal anesthesia had a reduced incidence rate of AKI; however, the difference was not statistically signi cant. 17 In their meta-analysis, Joanne Guay et al found that compared with general anesthesia, there was a reduction in postoperative mortality when spinal anesthesia was used. 18 However, the difference in patients' mortality rate after the use of general anesthesia and general anesthesia plus spinal anesthesia was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation